PENGARUH LOGO BARU PT. TELKOM, Tbk TERHADAP CITRA PERUSAHAAN - Febriansyah, Febriansyah; Nabila, Nuzul Inas (Journal of Innovation in Business and Economics, 2014)
This study aimed to determine to what extent rebranding had effect on corporate reputation. Through the implementation of quantitative research design, this project involved Telkom customers of Bandar Lampung as population where the sampling technique applied was non-probability sampling and purposive sampling approach. The research instruments were questionnaires which were handed out to 100 customers of Telkom Bandar Lampung during May 2013 period. Afterward, the data were analyzed using simple regression analysis. The results showed the value of R square of company rebranding was 0.235 which indicated that the contribution X variable (rebranding) played significant role in influencing each additional of Y variable at 23.5% for corporate reputation while 76.5% were influenced by other factors. Further, hypothesis test results signified that t-test 5,486 was greater (>) than t-table 1,984 so that it can be concluded that rebranding had significantly affect Telkom Ltd. corporate reputation in Bandar Lampung.